The effect of quality of worklife and job satisfaction on organizational commitment - Sri Marti Pramudena; Asmy Fuzita Hilda (STIE Binaniaga, 2019)
This study aims to determine the effect of work life quality and job satisfaction on organizational commitment. Collection research data through interviews, observation, and distribution of questionnaires to 110 respondent. The sample in this study were employees who worked at PT. Intrasari Raya Bogor. The sampling method uses simple random sampling. The research data was analyzed using the SPSS version 20. The results showed that work life quality and job satisfaction on organizational commitment had a positive and significant effect, both partially and simultaneously where t-value 4.694>t-table 1.6592 and F-value 31.054>F-table 3.08. Organizational commitment of 64.5% is influenced by other variables not included in this study. Companies are expected to be able to think of other strategies in implementing quality work life and increasing employee satisfaction so as to create strong employee commitment. Keywords: Quality of Work Life, Job Satisfaction, Organizational Commitment